Kajian Teologi Misi Terhadap Pemuridan Bagi Remaja Di Jemaat GMIM Nafiri Tempang Wilayah Langowan Dua - Ratag, Linda P.; Tambingon, Miryam (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2022)
The church, guided by the power of the Holy Spirit, is a tool for God's mission and the church is given a mandate to carry out every task, namely witnessing, fellowship and service. The services provided by the church must be effective because church attendance is very important if the church is to carry out God's mission as the basis for His testimony in the world, including discipleship. Discipleship is the core ministry of the church and through discipleship will bring a person to know God more and more as Lord and Savior of life. Discipleship is carried out in all circles, including teenagers. Teenagers really need discipleship services because many problems arise including smoking, consuming alcohol, early marriage and so on. The method used in this study uses a qualitative method. Data collection was carried out by in-depth interviews. Through the result of the research obtauned, the researcher hopes that parents and the church must play a role in the process of growth and development of adolescent spir ituality and provide creative and effective discipleship services so that teenagers do not easily fall into deviant behavior.